WORKSHOP KEWIRAUSAHAAN MEMBANGUN BISNIS MELALUI PENERAPAN TEKNOLOGI DIGITAL - Chowal Jundy Kumoro; Lambok Rommy Sulaeman; Rizaldi Putra; Memet Sanjaya; Deni Utama; Putri Nurazizah; Davina Clarissa Rabbani; Neng Siti Fathimah (JURNAL PENGABDIAN MANDIRI, 2025)
The high unemployment rate in Bekasi Regency, reaching 9.37% in 2023, presents a pressing issue amidst the region's rapid industrial development. Intense job market competition and the low entrepreneurial interest among senior high school and vocational students further narrow opportunities for youth to achieve economic independence. This community service program aims to foster entrepreneurial spirit and enhance digital competencies among students through a workshop titled “Entrepreneurship Workshop: Building a Business through the Application of Digital Technology.” The workshop was conducted in person at Takumi Polytechnic using a participatory and hands-on approach, including activities such as Business Model Canvas development, digital brand creation, and simulations of digital marketing via social media and online platforms. A total of 78 students from various high schools and vocational schools in Bekasi participated in the program. The results showed a significant improvement in students’ understanding of digital entrepreneurship concepts, as indicated by higher post-test scores and their ability to design and pitch tech-based business ideas. Evaluation data revealed that 91% of participants expressed interest in launching their own digital ventures after the training. The workshop not only expanded entrepreneurial awareness but also led to the establishment of a follow-up community called Digitalpreneur Muda Bekasi as a platform for collaboration and peer learning. This program is expected to serve as a replicable model for digital entrepreneurship education and contribute to local economic development through youth-led innovation